Peningkatan Kemampuan Memahami Pembacaan Cerpen Melalui Model Pembelajaran Berpikir Induktif Dengan Media Film Pendek - Hetti Nurbaety (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2021)
This study uses a classroom action research design consisting of planning, action, observation, and reflection. The research subjects were 32 students. Collecting data using direct observation, interviews, teacher and student journals and written tests. The results of the study on student activity increased from 69% in cycle 1 to 74% in cycle 2. Increased activity in PBM increased from 61.36% in cycle 1 to 80% in cycle 2. Increased student activity in carrying out evaluations of students' ability to master the material learning. This is based on the results of the evaluation of 76 in cycle 1 which increased to 81 in cycle 2. Based on the explanation above, it can be concluded that learning to understand reading short stories through an inductive thinking learning model with short film media is proven to improve the ability to understand reading short stories for class XI AKL students at SMK Negeri 3 Linggabuana Purwakarta.